Cover Image, Volume 115, Number 3, March 2018. Issue 3 (29th January 2018) - Gruber, Pia; Carvalho, Filipe; Marques, Marco P. C.; O'Sullivan, Brian; Subrizi, Fabiana; Dobrijevic, Dragana; Ward, John; Hailes, Helen C.; Fernandes, Pedro; Wohlgemuth, Roland; Baganz, Frank; Szita, Nicolas
Abstract : The cover image, by Pia Gruber et al., is based on the Article Enzymatic synthesis of chiral amino‐alcohols by coupling transketolase and transaminase‐catalyzed reactions in a cascading continuous‐flow microreactor system, DOI:10.1002/bit.26470 . Design Credit: Winter Mraz, Frozen Ink Designs.